Measuring Power and Satisfaction in Societies with Opinion Leaders: An Axiomatization - Rene van den Brink; Agnieszka Rusinowska; Frank Steffen (Tinbergen Institute, 2011)
A well-known model in sociology and marketing is that of opinion leadership. Opinion leaders are actors who are able to affect the behavior of their followers. Hence, opinion leaders have some power over their followers, and they can exercise this power by influencing their followers choice of action. We study a two-action model for a society with opinion leaders. We assume that each member of the society has an inclination to choose one of these actions and that the collective choice is made by simple majority of the actions chosen by each member. For this model we axiomatize satisfaction and power scores, which allow us to investigate the effects of different opinion leader-follower structures.
Keywords: D71; D85; 330; Collective choice; follower; influence; opinion leader; power; satisfaction; axiomatization; Öffentliche Meinung; Macht; Politische Willensbildung; Neue politische Ökonomie; Theorie